Navigating in large hospitals - Hughes, Nancy; Pinchin, James; Brown, Michael; Shaw, Dominick E. (2015)
Navigating around large hospitals can be a stressful and time-consuming experience for all users of the hospital infrastructure. Navigation difficulties encountered by patients and visitors can result in missed appointments or simply create a poor impression of the hospital organisation. When staff encounter navigation difficulties this can lead to cost and efficiency issues and potentially put patient safety at risk. Despite the provision of an array of in-hospital navigational aids, ‘getting lost’ continues to be an everyday problem in these large complex environments. This study aims to to identify factors which affect navigation in hospitals. We do not seek to evaluate the effectiveness of a single navigation aid, instead the objective of this study was to understand the environment in which a new system must operate and the gaps in provision left by existing navigation aids. This study is intended to be used to inform the development of new in hospital navigational aids, be they technological or otherwise. Eleven participants, all users of a large hospital site, were asked to describe specific first hand experiences of navigating in a hospital. The ‘Critical Incidence Technique’ was applied in a series of semi-structured interviews to elicit information about a participants navigation experience. This work presents the results of these interviews, with concepts identified and organised into five themes: The ‘Impact’ of poor navigation, ‘Barriers’ to effective navigation, ‘Enhancers’ for effective navigation, ‘Types of Navigation Aids’ and user groups with ‘Specific Navigational Needs’. The number of navigation aids available to participants was identified as an issue in itself, we found examples of thirty seven distinct sources of information available to a hospital user. We begin by introducing previous work on in-hospital navigation before describing the study design employed in this research. The themes and categories identified from the interview data are enumerated and described, with examples given from the interview transcripts. Finally we go on to give a discussion of some potential navigation solutions in light of the identified factors. This study highlights that a candidate navigation aid must be carefully designed and implemented if it is to compliment the thirty seven other sources of navigation information available to the hospital user.